Hubungan kebiasaan bermain game online dan konformitas teman sebaya dengan motivasi belajar peserta didik sekolah dasar se-kecamatan wonosegoro - Ichsanudin, Amin; Riyadi, Riyadi; Wahyuningsih, Siti (Universitas Sebelas Maret, 2025)
This study aims to find out whether there is a relationship between online gaming habits and peer conformity with learning motivation. The research design is quantitative with an ex-postfacto correlational research method. The data collection technique used was a questionnaire distributed to students of the state elementary school in Wonosegoro district. The results of this study are 1) there is a significant negative relationship between the habit of playing online games and learning motivation at a